POTRET PERKEMBANGAN DAN PRAKTIK KEUANGAN ISLAM DI DUNIA - Nur Kholis (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2017)
Islamic finance has become a global phenomenon characterized by an increasing number of Islamic financial institutions and has had a positive impact on financial development in a world that promotes universal moral values; justice, honesty, and ethics. Various scientific studies have proved that Islamic finance is more resilient to the financial crisis, so it is expected that the implementation of Islamic finance will prosper in a fair and equitable. The era of globalization and the phenomenon of the development of financial economics in the world has spawned many opportunities as well as challenges, especially in efforts to develop Islamic finance. Therefore, the development of Islamic financial economy in the future, in addition to learning from the success and failure of conventional financial economy with various crises that occur, should also take advantage of new approaches that are creative and innovative. –(Keuangan Islam telah menjadi fenomena global yang ditandai dengan semakin banyaknya lembaga keuangan Islam dan memberikan dampak positif bagi perkembangan keuangan di dunia yang mengedepankan nilai-nilai moral universal; keadilan, kejujuran, dan etika. Berbagai kajian ilmiah telah membuktikan bahwa keuangan Islam lebih tahan terhadap krisis keuangan, sehi ngga diharapkan penerapan keuangan Islam akan mensejahterakan secara adil dan merata. Era globalisasi dan fenomena perkembangan ilmu ekonomi keuangan di dunia telah melahirkan banyak peluang sekaligus tantangan, terutamanya dalam upaya pengembangan keuangan Islam. Oleh karena itu, pengembangan ekonomi keuangan Islam ke depan, selain perlu belajar dari kesuksesan dan kegagalan ekonomi keuangan konvensional dengan berbagai krisis yang terjadi, perlu juga memanfaatkan pendekatan-pendekatan baru yang kreatif dan inovatif.)– Keywords: Islamic Finance, World Finance, and Financial Institutions.